Opening government for public scrutiny: A critique of recent efforts to make governance in India more transparent and accountable - Jain, R.B. (2006)
Realising that the secrecy and the lack of openness in official transactions, a colonial legacy which somehow persisted through the five decades of India's Independence, was responsible for corruption in administration, apart from being contrary to the spirit of an accountable and democratic Government, the Government of India addressed itself to the problem of ensuring freedom of information to the public and to amend such laws that stipulate necessary access of the public to information. As a result a number of statutory schemes were formulated to amend various existing central and state legislations in order to improve the access of public to information from public offices, through streamlining of internal procedures, computerisation, and by setting up public facilitation counters in offices by the Government of India and the governments in various states of the Indian federation. - Reproduced.
Keywords: Public administration